Influence of the cultural context on the development of science in Russia: socialpsychological perspective - V. I. Konnov (Vestnik MGIMO-Universiteta)
The article offers a socialpsychological perspective on the process of shaping national science culture, which determines the peculiarities of scientific research in different countries. This point of view allows to determine the causes for emergence of national scientific cultures and provides instruments to describe them. The author applies the three-level scheme for describing cultures, developed by D. Oyserman and coauthors, and attempts to analyze the distal level of the Russian scientific culture, constituted by the influence of the Russian cultural tradition, which forms the context for the work of Russian scientists.